A new ZVT-ZCT quasi-resonant DC link for soft switching inverters - Urgun, S.; Erfidan, T.; Bodur, H.; Cakir, B. (TAYLOR & FRANCIS LTD, 2010)
In this article, the new ZVT-ZCT Quasi-Resonant DC Link, which ensures zero crossings at any time required for soft switching (SS) and provides zero voltage transition (ZVT) turn-on and zero current transition (ZCT) turn-off together for the main switch of active snubber cell in pulse width modulated or space vector modulated operation of inverter is presented. The new circuit combines the most desirable features of the circuits presented previously and overcomes most drawbacks of these circuits by using only one auxiliary switch with fewer other components. Consequently, new ZVT-ZCT Quasi-Resonant DC Link, which is verified by a prototype of a 1.2 kW and 50 kHz circuit, is analysed in detail. All semiconductor devices operate under SS, the main switch is subjected to no additional voltage and current stresses, and the stress on the auxiliary switch is very low in the proposed new inverter.
Keywords: soft switching; zero current transition; zero voltage transition; PWM inverter; quasi-resonant dc link; CONVERTERS; Engineering